POPULARITAS ANIMASI UPIN IPIN PADA ANAK-ANAK DI BALI - Gede Lingga Ananta Kusuma Putra (Jurnal Nawala Visual, 2019)
Animation is one of the media affected by technological development. As technology develops, animation can now be done through a computerized system. Upin and Ipin is one of the animations created through a computerized system and is favored by children. This animation produced in Malaysia has a simple, easy to digest everyday story and has an attractive three-dimensional visual display. This study aims to analyze what 3-dimensional animation and its opportunities to the audience, especially children. The study data collection was done through observation of several children who are always bound to watch animation. The analysis shows that children especially in Bali are quite interested in 3-dimensional animation, one of which is Upin Ipin animation. Interest in 3-dimensional animation, especially Upin Ipin, is quite influential for children. The most visible influence is in the form of daily behavior, as well as Malay dialect and dialect when talking to his friends, parents, and people around him. In fact, due to the influence of Upin Ipin, the words and sentence structure expressed are not like the sentence structure in Indonesian in general. This phenomenon implies that 3-dimensional animation has a good opportunity to be developed, the indicator is that children are very enthusiastic and interested in 3-dimensional animation.